Longitudinal field test assessment in a Basque soccer youth academy: A multilevel modeling framework to partition effects of maturation - Bidaurrazaga-Letona, I.; Carvalho, H. M.; Lekue, J. A.; Santos-Concejero, J.; Figueiredo, A. J.; Gil, S. M. (International Journal of Sports Medicine, 2015)
The purpose of the study was to examine the effect of age on short-term performance indicators applying multilevel regression modeling, and whether changes induced by age were affected by maturation. The study applied a mixed longitudinal approach with 8 measurement points over a period of 4 years. Anthropometry, predicted adult stature, countermovement jump, 15-m sprint and agility test from 38 under-11 young soccer players were considered. Early maturing players were 3% taller compared to late maturers. A substantial effect of age was present in all performance indicators (P<0.05). Parameters showed improvements in performance, even when accounting for interindividual variation in somatic maturity. Vertical jump tended to be stable in early maturers during the first year, presenting an exponential increase thereafter (16%, P<0.05). Additionally, early maturing boys had lower vertical jump scores but a substantial higher rate of development with age (3% per year). Performance tends to plateau during the first 3 years following the improvements in agility (9.1%, P<0.05). In the running tests, early maturers had better performances (19%, P<0.05), while a higher rate of improvement of 1% was observed for the late maturers. Young soccer players should be expected to have substantial improvements in short-term performance, influenced by independent variation between players in maturity status.